PROGRAM “EDUKREASI” (EDUKASI DAN REKREASI) SEBAGAI UPAYA MENINGKATKAN SELF-EFFICACY PADA REMAJA DI PANTI ASUHAN X - Dzikrina I. Ramadhani; Frillian R. Beresaby; Siti N. Noviyanti; Astri A. Hapsara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Adolescence is a developmental phase vulnerable to psychosocial challenges, particularly among adolescents living in orphanages. This study aimed to identify changes in adolescents’ self-efficacy after participating in an experiential learning intervention. The study employed a quantitative involving 20 adolescents at X Orphanage Jakarta, consisting of 6 males and 14 females aged 13–18 years. Data were collected using a Self-Efficacy Scale and observation. The results indicated an increase in self-efficacy, particularly in the strength dimension from 22,2 to 22,65 and the generality dimension from 6,25 to 6,6. Observational findings also demonstrated positive behavioral changes, including increased bravery, social participation, trying to completing challenges. These findings indicate that group-based interventions have the potential to contribute positively to the development of self-efficacy among adolescents living in orphanages.